2018
DOI: 10.1111/aos.13986
|View full text |Cite
|
Sign up to set email alerts
|

Standard cross‐linking versus photorefractive keratectomy combined with accelerated cross‐linking for keratoconus management: a comparative study

Abstract: Purpose To compare the safety and efficacy of standard 30 min epithelium‐off cross‐linking ( CXL ) versus photorefractive keratectomy ( PRK ) combined with accelerated epithelium‐off cross‐linking ( AXL ) for the treatment of progressive keratoconus ( CXL ‐Plus). Methods This study was a prospective multicentre comparative clinical study. A total of 125 eyes of 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Furthermore, Iqbal et al28 compared SCXL versus CXL Plus (combined ACXL and photorefractive keratectomy). They finally concluded that SXCL had close outcomes to CXL Plus at 24-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Iqbal et al28 compared SCXL versus CXL Plus (combined ACXL and photorefractive keratectomy). They finally concluded that SXCL had close outcomes to CXL Plus at 24-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is more accepted and preferred all over the world as being a safer and more effective method in the long term. 93 , 94 …”
Section: Advances In Treatmentmentioning
confidence: 99%
“…Kanellopoulos et al initially showed same-day topography-guided PRK with CXL as more effective for visual rehabilitation (as incorporated into the Athens protocol), with subsequent studies corroborating increased efficacy of simultaneous CXL and PRK compared with CXL alone [4045]. However, a recent prospective multicenter study comparing conventional CXL (Dresden protocol) to simultaneous combined PRK and CXL (Athens protocol) showed nearly equivalent results in visual outcomes and refractive improvement after 2 years, suggesting that there may not be a significant benefit with the Athens protocol over the longer-term refractive advantages of the conventional protocol [46]. Primary considerations for planning simultaneous combined CXL and PRK concern ablation depth and corneal thickness, so most protocols specify a maximum ablation depth between 50 and 80 μm [34, 41, 42].…”
Section: Combined CXL Procedures For Refractive Correction (Cxl Plus)mentioning
confidence: 99%
“…For combined CXL with PRK (Athens protocol), there is consistent level 4 evidence that shows its safety and efficacy. However, there is some controversy within level 3 studies that suggest the longer-term results may not be significantly improved compared with CXL alone [44, 46]. For this reason, we offer a grade C recommendation for this procedure.…”
Section: Grade Practice Recommendationsmentioning
confidence: 99%